Non-adiabatic coupling and conical intersection(s) between potential energy surfaces for HeH2+. (17th June 2020) - Gupta, Ankur Kumar; Dhindhwal, Vikash; Baer, Michael; Sathyamurthy, Narayanasami; Ravi, Satyam; Mukherjee, Soumya; Mukherjee, Bijit; Adhikari, Satrajit
Abstract : By computing the non-adiabatic coupling terms and the adiabatic-to-diabatic transformation angle along closed contours in nuclear configuration space using the CASSCF method and the aug-cc-pVTZ basis set for the lowest three electronic states of HeH2 +, we explore the conical intersection between states in near collinear and noncollinear geometries, particularly in the C 2v geometry. GRAPHICAL ABSTRACT: